Clinical usefulness of conversion surgery for unresectable pancreatic cancer diagnosed on multidetector computed tomography imaging: Results from a multicenter observational cohort study by the Hokkaido Pancreatic Cancer Study Group (HOPS UR‐01). Issue 5 (9th July 2019) - Kimura, Yasutoshi; Nakamura, Toru; Hayashi, Tsuyoshi; Kuwatani, Masaki; Motoya, Masayo; Yoshida, Makoto; Imamura, Masafumi; Nagayama, Minoru; Yamaguchi, Hiroshi; Yamakita, Keisuke; Goto, Takuma; Sakuhara, Yusuke; et al.
Abstract: Background and Aim: Effective multidisciplinary approaches for unresectable pancreatic cancer (UR‐PC) that include modern chemotherapeutic regimens and subsequent conversion surgery (CS) are being developed. The aim of this study was to evaluate outcomes of patients clinically diagnosed with UR‐PC, focusing on the efficacy of CS. Methods: Patients ineligible for two multicenter phase II studies conducted by the Hokkaido Pancreatic Cancer Study Group (HOPS) were recruited. Sequential treatment regimens, conversion to radical surgery, and overall survival (OS) were analyzed by multidetector computed tomography (MDCT)‐based UR factors. Univariate and multivariate analyses were performed to identify predictors of OS. Results: Sixty‐six of 247 intended recruits for HOPS studies from October 2013 to April 2016 were included. Unresectability was due to locally advanced (LA) disease and metastasis (M) in 42 and 24 patients, respectively. Induction therapy began with chemotherapy (CT) and chemoradiotherapy (CRT) in 44 and 17 patients, respectively, of whom 23 received modern CT regimens. Radical surgery was completed in 12 (LA, 10; M, two) with a median treatment interval of 10.3 months (range, 2‐32). Eleven patients (91.6%) achieved pathological R0 resection. Median OS was significantly longer in patients who underwent CS than those who did not (44.1 vs 14.5 months, P  < 0.0001). CS was an independent predictor of OS (hazard ratio, 0.078; 95% confident interval, 0.017‐0.348; P  =   0.001). Conclusion: Conversion surgery after a favorable response to sequential treatment might prolong survival in patients with UR‐PC. Precise diagnosis on MDCT followed by sequential multimodal anticancer treatment is essential. Abstract : Kaplan‐Meier plots for survival by CS status and reason for initial unresectability. Overall survival of patients who completed CS was significantly longer than those who did not (44.1 vs 14.5 months, P  < 0.0001).